2016
DOI: 10.1007/s12603-015-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

Why is later age at retirement beneficial for cognition? Results from a French population-based study

Abstract: Although our results are in accordance with previous studies (i.e., older age at retirement is associated with decreased risk of dementia), it provides additional information regarding the possible explanation for such results. Given that a longer working life did not reduce the risk of dementia, the age at retirement cannot be considered as a new factor of cognitive reserve but rather seems to be a psycho-social vulnerability factor. Further evidence is necessary to identify work and retirement related factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…According to the literature, a later age of retirement is related to decreased dementia risk, including later onset of AD, 5‐8 and better preserved cognitive function 20 . The results from the present study, showing that a higher age of retirement is associated with a reduced risk of dementia, are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…According to the literature, a later age of retirement is related to decreased dementia risk, including later onset of AD, 5‐8 and better preserved cognitive function 20 . The results from the present study, showing that a higher age of retirement is associated with a reduced risk of dementia, are consistent with these earlier findings.…”
Section: Discussionsupporting
confidence: 91%
“…A common explanation for why delaying retirement may be beneficial for cognitive health is that retirement may be associated with a drop in mental and social stimulation. Accordingly, it has been proposed that people who work for a longer time keep up their cognitive level for a longer period, thereby reducing the risk of dementia diseases or delaying its onset 5‐8 . As such, the results are consistent with a “use it or lose it” perspective and the cognitive reserve hypothesis 2,21 …”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Accordingly, retirement may be a potential trigger for cognitive decline, assuming that retirees leave paid work that is cognitively demanding. Many studies have supported this assumption showing that retirement is associated with lower cognitive functioning [ 18 23 ], and later retirement is associated with better cognition and lower risk of dementia [ 24 27 ], although some studies have found no association [ 28 , 29 ] or even a positive effect [ 30 ] of retirement on levels of cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, some studies suggested that a late retirement and thus remaining longer in the stimulating occupational environment may help preserving cognitive functioning and to delay cognitive impairments in old age (e.g. Lupton et al, 2010;Bonsang et al, 2012;Mazzonna and Peracchi, 2012;Dufouil et al, 2014;Grotz et al, 2016). Yet, some authors argued that such effects of timing of retirement on late-life cognition may be overestimated (e.g.…”
Section: Introductionmentioning
confidence: 99%